Brain calciﬁcations and perilesional edema - Javier Pretell, E. (2007)
Brain calciﬁcations, most frequently due to residual cysticercosis, are very common in developing countries. Recent reports have shown that residual brain lesions may be enhanced after contrast and present edema after an episode of neurological symptoms. We report three cases showing this phenomenon and how it can complicate the diagnosis, increasing hospital stay, and sometimes requiring invasive diagnostic procedures. Calciﬁcations with surrounding edema must be considered in the differential diagnosis of enhancing brain lesions.